An investigation of perception gap of reverse logistics service quality: the case of mobile phone industry. (18th January 2007) - Lee, Tzong-Ru; Chang, Hsiu-Yu; Chen, Shiou-Yu
In the current competitive market, many enterprises face the fierce competitions that are between the companies and also between supply chains. From the whole supply chain point of view, complete circulating logistic systems must include forward logistics and Reverse Logistics (RL). This study uses the PZB Model and the reverse logistics service models to analyse service quality and customer satisfaction in the mobile phone industry. The following are the enumeration identified by this study. There are six priority improvements for enterprises: (1) transparent price for accessories and repair, (2) high zeal for solving the recycle of accessories, (3) free charge for product upgrade and service within the warranty period, (4) convenient product return and exchange service, (5) free checking of the function and (6) active notice after repair.